Optimizing Outcome: Use of a Checklist for Otolaryngologists Overseeing Ex Utero Intrapartum Treatment (EXIT). (23rd August 2013) - Yau, Yuk Y. A.; Camilon, Felizardo; Ahuja, Gurpreet S.; Camilon, Philip R.; Pham, Nguyen
Abstract : Objectives: Evaluate elements necessary in the decision making and execution during ex‐utero intrapartum treatment (EXIT) and operation on placental support (OOPS) procedures to ensure superior outcomes. Methods: Retrospective review of neonatal head and neck obstruction cases from January 1998 to January 2013 at two tertiary referral centers. Main outcome measures: Data regarding prenatal care, delivery details, pathology of lesion, and postnatal course. Results: From 1998‐2013, 13 of the 15 cases of prenatally‐diagnosed potentially severe head and neck obstruction used an EXIT or OOPS procedure to secure the airway. The decision making process leading to whether an EXIT procedure needed to be performed was reviewed. Additionally, we analyzed elements that must be addressed in the checklist, including defined tasks for the specialties of perinatology, neonatology, anesthesia, fetal imaging, pediatric otolaryngology, and operative services to optimize outcome. Equipment and space needs are addressed as well. Multidisciplinary rehearsal of the procedure is strongly recommended, with the pediatric otolaryngologist leading the process. We offer a comprehensive checklist for the otolaryngologist overseeing such procedures. Conclusions: Medical checklists are increasingly being used to ensure safety and improve outcomes in complex patient care situations. Obstructive masses of the head and neck in the fetus present a difficult and potentially fatal clinical problem. Based on our experience, we offer the otolaryngologist a structured and well‐choreographed approach in dealing with such complex situations, with the incorporation of a comprehensive checklist for EXIT procedures.